Early Morphological Growth Response and Incidence of Key Pests Under Two Spacing Regimes of Coffea canephora - Godfrey Sseremba; Godfrey Hubby Kagezi; Judith Kobusinge; David Akodi; Nicholas Olango; Joseph Mulindwa; Pascal Musoli; Geofrey Arinaitwe (Indonesian Coffee and Cocoa Research Institute, 2021)
Coffea canephora has non-limiting but unexploited yield and quality potential when compared with C. arabica. Coffee tree density optimization can improve fortunes of smallholder farmers. An attractive example is that high productive countries where high plant densities do increase area yield but across boardrecommendations are illogical especially with variety and agroecological variations. We aimed to compare two spacing regimes for growth response and pest incidence using Kituza Robusta clone. Randomized complete block designs with three replications and eight plants per plot were established at four agroecologically diverseon-farm locations. Eleven plant growth variables were measured. In addition incidences of five key pests were assessed. Data was collected on a 3-month interval starting from 12 up to 21 months after planting. Highly significant differences between spacing regimes (p<0.01) were obtained for majority of variables. Mean growth response was generally higher under 3 m x 1 m (high density) than 3 m x 3 m (low density) particularly with stem girth, plant height, length of longest primary branch, and leaf blade length. Conversely, pest incidence of black coffee twig borer, leaf eating beetles, leaf miners, and tailed caterpillars, except skeletonizers was higher under high than low plant densities. The findings provide aguide on implications of high plant densities on growth robustness which is translatable into yield potential; amidst a pest prevalence dilemma in studied type of C. canephora.